Comparing meditative scuba diving versus multisport activities to improve post-traumatic stress disorder symptoms: a pilot, randomized controlled clinical trial. Issue 1 (31st December 2022) - Gibert, Lionel; Coulange, Mathieu; Reynier, Jean-Charles; Le Quiniat, Frédéric; Molle, Aymeric; Bénéton, Frédéric; Meurice, Vincent; Micoulaud, Jean Arthur; Trousselard, Marion
ABSTRACT: Background: Post-Traumatic Stress Disorder (PTSD) is a chronic and disabling disease that currently has no fully effective therapeutic solution. Complementary approaches, such as relaxation, sport, or meditation, could be therapeutic aids for symptom reduction. Scuba diving combines sport and mindfulness training and has been found to have a positive effect on chronic stress and PTSD. Objectives: The first objective of this pilot study is to compare the effectiveness of diving associated with mindfulness exercises (the Bathysmed® protocol) with multisport activity in reducing PTSD symptoms. The secondary objective is to compare the impact of the Bathysmed® protocol on mindfulness functioning in the two groups of subjects suffering from PTSD. Method: This proof-of-concept took the form of a controlled randomized clinical trial. The primary endpoint was the severity of PTSD symptoms, measured by the PCL-5 (PTSD Check List) scale. Half of the group were exposed to the Bathysmed® protocol (the experimental condition), and the other half to a non-specific multisport program. Results: Bathysmed® protocol improved PCL-5 scores more than the multisport program but the result was not significant. The protocol was significantly better than the multisport activity in reducing intrusion symptoms of PTSD after one month. Globally, trait mindfulness scores improved up to one month after the course, but the result was not significant. Three months after the course, there was no difference between the two groups with regard to PCL-5 and Freiburg Mindfulness Inventory scores.. Conclusion: Our study demonstrates the value of the Bathysmed® protocol even though it suffers from a lack of power and could only obtain partial but encouraging results. Mindfulness must be practiced over the long term to achieve stable benefits. This probably explains why no differences persisted three months after the course. Further work is needed to confirm the initial results obtained with this pilot study. HIGHLIGHTS: Meditative scuba diving improved overall PTSD symptoms after one month more than multisport activity but not significantly. PTSD Intrusion symptoms were significantly improved after one month by the meditative diving. The positive effects of meditative diving faded after 3 months.